KAJIAN PERSEPSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN DI KOTA KENDARI - Candra Puspita Ningtyas; Munawir Makmur; Muammar Makmur (Halu Oleo University, 2023)
In the context of the property market, consumer perceptions can be influenced by factors such as location, price, facilities, design and housing brand. Therefore, understanding consumer perceptions can help developers design housing products that suit consumer needs and desires, thereby increasing consumer interest in purchasing housing products. This research seeks to determine consumer perceptions of housing purchasing decisions in Kendari City. This research uses descriptive quantitative research methods. The research results show that the calculated F value is 28.695> the F table value is 2.463 and the sig value. namely 0.0000<0.05, then Ho is rejected and Ha is accepted, meaning that the variables of location, price, product quality and promotion influence consumer decisions. The calculated t value of the price variable influences consumer decisions in purchasing housing in Kendari City. The influence of price on housing purchasing decisions shows that the price factor has a significant role in the consumer decision-making process. The location, product quality, and promotion variables have no effect on consumer decisions when purchasing housing in Kendari City.